2010
DOI: 10.1519/jsc.0b013e3181ddfae7
|View full text |Cite
|
Sign up to set email alerts
|

An Electromyography Analysis of 3 Muscles Surrounding the Shoulder Joint During the Performance of a Chest Press Exercise at Several Angles

Abstract: This study compared the activation of the clavicular head and the sternocostal head of the pectoralis major and the anterior deltoid when performing the bench press at several different angles. Fifteen healthy male subjects participated in this study. Subjects performed the chest press exercise at 0 (flat bench), 28, 44, and 56 degrees above horizontal using 70% of their respective 1 repetition maximum for each angle. Electromyographic activity was recorded during each repetition. Activation of the clavicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
61
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(90 citation statements)
references
References 6 publications
16
61
4
4
Order By: Relevance
“…Divergent results were also cited in the study by Treb et al [4], in which the activation of the sternocostal part was significantly higher in the incline bench press compared with horizontal bench press, thus showing that the greater the angle of the exercise, the stronger the activation of this part of the muscle.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Divergent results were also cited in the study by Treb et al [4], in which the activation of the sternocostal part was significantly higher in the incline bench press compared with horizontal bench press, thus showing that the greater the angle of the exercise, the stronger the activation of this part of the muscle.…”
Section: Discussionmentioning
confidence: 81%
“…However, in the study by Barnett et al [19], the clavicular part showed a similar activity for the incline and the horizontal bench press and it showed less activity during the decline bench press. Trebs et al [4] observed that the clavicular part showed a significantly higher activity in the incline bench press compared with the horizontal modality. These differences can be explained by the angle of inclination of the exercise and by the hand spacing adopted in the different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences are associated with a decrease in velocity and the appearance of the sticking region. Deceleration was higher in lifts with the maximal load, which may have been caused by diminishing potentiation of the contractile elements (Walshe et al 1998;Konrad 2005;Reynolds et al 2006;Trebs et al 2010). Furthermore, the difference in lifted weight was strongly associated with a significant increase in bioelectrical activity of all the studied muscles.…”
Section: Discussionmentioning
confidence: 87%
“…Identifica-se também na literatura, que no supino convencional (fitness) o deltóide anterior pode apresentar uma maior ativação que o músculo peitoral maior, devido à angulação do banco na execução do exercício ou com a elevação na carga (Sadri et al 2011, Wattanaprakornku et al 2011Trebs, Brandenburg & Pitney 2010).…”
Section: Resultsunclassified